Four-Dimensional Computed Tomography Scanning for Dynamic Wrist Disorders: Prospective Analysis and Recommendations for Clinical Utility - Carr, Renee; MacLean, Simon; Slavotinek, John; Bain, Gregory I. (Journal of Wrist Surgery, 2019)
Background Four-dimensional computed tomography (4D CT) is a rapidly developing diagnostic tool in the assessment of dynamic upper limb disorders. Functional wrist anatomy is incompletely understood, and traditional imaging methods are often insufficient in the diagnosis of dynamic disorders.Technique This study has developed a protocol for 4D CT of the wrist, with the aim of reviewing the clinical utility of this technology in surgical assessment. A Toshiba Aquilion One Vision scanner was used in the protocol, in which two- and three-dimensional “static” images, as well as 4D “dynamic” images were produced and assessed in the clinical context of each patient. These consisted of a series of multiple 7-second movement clips exploring the nature and range of joint motion.Patients and Methods Nineteen patients with symptoms of dynamic instability were included in the study. Patients were assessed clinically by two orthopaedic surgeons, and qualitative data were obtained from radiological interpretation.Results The study demonstrated varied abnormalities of joint movement attributed to a range of wrist pathology, including degenerative arthritis, ligamentous injuries, Kienbock's disease, and pain following previous surgical reconstructive procedures. Interpretation of the 4D CT scan changed the clinical diagnosis in 13 cases (68.4%), including the primary (15.8%) or secondary diagnosis (52.6%). In all cases, the assessment of the dynamic wrist motion assisted in understanding the clinical problem and led to a change in management in 11 cases (57.9%). The mean effective radiation dose for the scan was calculated at 0.26 mSv.Conclusion We have found that the clinical utility of 4D CT lies in its ability to provide detailed information about dynamic joint pathology not seen in traditional imaging, targeting surgical treatment. Limitations to the use of 4D CT scan include lack of availability of the technology, potential radiation dose, and radiographer training requirements, as well as limited understanding of the nature of normal motion.
Keywords: 4D CT; four-dimensional computed tomography; dynamic CT; dynamic wrist disorders; dynamic instability disorders